Influenza vaccine coverage and factors associated with non-vaccination among caregiving and care-receiving adults in the Canadian Longitudinal Study on Aging (CLSA) - Katie Gravagna; Christina Wolfson; Nicole E. Basta (BMC, 2024)
Abstract Background Influenza vaccination is recommended for those at increased risk of influenza complications and their household contacts to help reduce influenza exposure. Adults who require care often experience health issues that could increase the risk of severe influenza and have close contact with caregivers. Assessing influenza vaccination prevalence in caregivers and care recipients can provide important information about uptake. Objectives We aimed to (1) estimate influenza non-vaccination prevalence and (2) assess factors associated with non-vaccination among caregivers aged ≥ 45 years and among care recipients aged ≥ 65 years. Methods We conducted an analysis of cross-sectional data from the Canadian Longitudinal Study on Aging collected 2015-2018. We estimated non-vaccination prevalence and reported adjusted odds ratios with 95% confidence intervals from logistic regression models to identify factors associated with non-vaccination among caregivers and care recipients. Results Of the 23,500 CLSA participants who reported providing care, 41.4% (95% CI: 40.8%, 42.0%) reported not receiving influenza vaccine in the previous 12 months. Among the 5,559 participants who reported receiving professional or non-professional care, 24.8% (95% CI: 23.7%, 26.0%) reported not receiving influenza vaccine during the same period. For both groups, the odds of non-vaccination were higher for those who had not visited a family doctor in the past year, were daily smokers, and those who identified as non-white. Discussion Identifying groups at high risk of severe influenza and their close contacts can inform public health efforts to reduce the risk of influenza. Our results suggest sub-optimal influenza vaccination uptake among caregivers and care recipients. Efforts are needed to increase influenza vaccination and highlight the direct and indirect benefits for caregiver-care recipient pairs. Conclusion The proportions of both caregivers and care recipients who had not been vaccinated for influenza was high, despite the benefits of vaccination. Influenza vaccination campaigns could target undervaccinated, high-risk groups to increase coverage.